2014
DOI: 10.1155/2014/170921
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Foreign Exchange Networks: A Time-Varying Copula Approach

Abstract: Based on a time-varying copula approach and the minimum spanning tree (MST) method, we propose a time-varying correlation network-based approach to investigate dynamics of foreign exchange (FX) networks. In piratical terms, we choose the daily FX rates of 42 major currencies in the international FX market during the period of 2005–2012 as the empirical data. The empirical results show that (i) the distributions of cross-correlation coefficients (distances) in the international FX market (network) are fat-taile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 47 publications
(79 reference statements)
5
28
0
Order By: Relevance
“…Wang et al [9] and Keskin et al [37], we employ Kruskal's [38] algorithm to construct the MST network. The construction procedure of the MST is presented as follows.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [9] and Keskin et al [37], we employ Kruskal's [38] algorithm to construct the MST network. The construction procedure of the MST is presented as follows.…”
Section: Methodsmentioning
confidence: 99%
“…It is crucial information not only for understanding and describing the interaction behavior of complex financial systems but also for financial activities ranging from asset allocation and investment portfolio to risk management [2]. There is a huge body of literature on investigating the correlation structure of assets in financial markets, such as stock markets [3][4][5][6], foreign exchange markets [7][8][9], and international equity markets [10,11]. Furthermore, a high percentage of the literature concentrates on the study of correlation structure of international real estate securities markets (see, e.g., a review by Worzala and Sirmans [12] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Source: Own study 4.5. Average Path Lentgth (APL), (Wang et al, 2014) This indicator is defined as the average number of steps along the shortest paths for all possible pairs of network nodes. It measures the effectiveness of information flow or mass transport in a given network.…”
Section: Fig3 Average Insurers Strength In the Period Under Considementioning
confidence: 99%
“…First, financial time series is assumed to follow normal distribution when the correlation is calculated by the Pearson correlation coefficient, whereas numerous studies have shown that the return on financial markets is not subject to normal distribution (Bae, Karolyi, & Stulz, 2003;Durante, Foscolo, Jaworski, & Wang, 2014;Wang, Xie, Zhang, Han, & Chen, 2014). However, this method has some shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method has some shortcomings. First, financial time series is assumed to follow normal distribution when the correlation is calculated by the Pearson correlation coefficient, whereas numerous studies have shown that the return on financial markets is not subject to normal distribution (Bae, Karolyi, & Stulz, 2003;Durante, Foscolo, Jaworski, & Wang, 2014;Wang, Xie, Zhang, Han, & Chen, 2014). Second, the Pearson correlation coefficient only reveals linear correlations, and it ignores the heterogeneity of financial data at different times; therefore, it is difficult to accurately measure the tail correlation in a booming market and a recession market .…”
Section: Introductionmentioning
confidence: 99%